PENERTIBAN PEDAGANG KAKI LIMA DI KAWASAN PARIWISATA BUKITTINGGI BERDASARKAN PERATURAN DAERAH NOMOR 2 TAHUN 2024 : The Regulation of Street Vendors in the Bukittinggi Tourism Area Based on Regional Regulation Number 2 of 2024 - Mochammad Defin Febrian Paulo; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2026)
The presence of street vendors in the touristy locations of Bukittinggi City creates a contradiction between maintaining public order and supporting their economic life for local people. The management of street vendor impacts is a key function of the local government in controlling and regulating informal vending activities in public areas. This research examines the role of the Local Government in regulating street vendors in Bukittinggi Tourism Area based on Perda (Regional Regulation) Number 2 of 2024 concerning Public Order and Safety. This study is based on a normative legal methodology with statutory and conceptual methods. The results of this study demonstrate that the regulation serves as a legal foundation for policy-making, location designating by the Mayor, and its enforcement through administrative sanctions issued by regional police. But its application is not universal, mainly because the guidance, supervision, and integrated management are damaged. Thus, a broader and more durable approach is needed to reconcile public order and social justice.